FILSAFAT PENDIDIKAN JASMANI SEBAGAI LANDASAN PENGEMBANGAN PENDIDIKAN HOLISTIK DI SEKOLAH: STUDI LITERATUR - Siregar, Alvin Pahlevi; Hardiansyah, Dicky; Hadi, Chrisna Pradifta; Akbar, Daffa Mulia; Siregar, Ahmad Nur; Nurkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the philosophy of physical education as a foundation for the development of holistic education in schools through a literature review of various national and international journals published between 2016 and 2026. The research method used is a literature study with a qualitative descriptive approach. The data were collected from various scientific articles relevant to the topics of physical education philosophy and holistic education. The results of the study indicate that physical education not only plays a role in improving students’ physical abilities but also contributes to the development of mental, emotional, social, moral, and character aspects. Physical education also serves as a learning medium that creates balanced student development through physical activities, cooperation, discipline, and sportsmanship. Furthermore, the philosophical approach in physical education is considered relevant for implementation in modern education systems because it supports more humanistic learning oriented toward the holistic development of students’ potential. Therefore, the philosophy of physical education needs to be continuously developed as an essential component in creating healthy, active, and character-based education in schools.